Acklen's garden, Dawson, Yukon Territory, September 24, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "J.H. Acklen's garden. Dawson City. Sep 24th 98. These two pails of vegetables sold in Dawson for $53.75" Original image in Hegg Album 26, page 34.